Studies on lipid profile in patients with non insulin dependent diabetes mellitus - Choudhury, Md Manzurur Rahman Shah; Alam, Towhidul; Rahman, AKM Shahidur (KYAMC Journal, 2013)
Diabetes mellitus is a global health problem and is associated with abnormalities of lipids and lipoprotein metabolism in variable frequency. The aim of the present work was to study the lipid abnormalities in NIDDM patients. Dyslipidaemia is of special interest because to compare it between male and female NIDDM patients and as well as to see the impact between women of reproductive age group and post menopausal women. For this purpose total serum cholesterol, triglyceride, LDL-C, HDL-C and LDL/HDL ratio were determined of a total number of 160 subjects. Out of these 80 subjects were diabetic and 80 were non-diabetic control subjects of both sexes. In this study, the total serum cholesterol levels were higher in NIDDM than control subjects and showed significant statistical difference (P<0.05) between control and NIDDM subjects. The serum triglyceride levels were found higher amongst diabetics as compared to the normal healthy controls and showed statistically significant difference (P<0.05). Higher LDL-C levels were showed in NIDDM and revealed significant difference (P<0.05) in comparison to control non-diabetic subjects and NIDDM patients. HDL-C levels were found decreased in patients with NIDDM compared to controls. The findings in the patients with NIDDM between male and female revealed no significant difference (P>0.05) in mean TC, TG, HDL-C and LDL-C between male and female diabetic patient in unpaired t-test. With improvement of diabetic control some improvement of the lipid abnormalities can be achieved. Most studies have shown that improvement of lipid abnormalities occur with proper glycaemic control in patients with NIDDM. The atherosclerotic process in the diabetic patient is indistinguishable from that seen in the non-diabetic population but it begins earlier and is more severe. Risk factors associated with atherosclerosis in the non-diabetic subject appear to have a similar relation to coronary heart disease among diabetics. Further studies are necessary to confirm the present suggestions, studies involving more number of subjects, estimation of Hb AIC. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13516 KYAMC Journal Vol.2(1) 2011 pp.123-127